2008
DOI: 10.1261/rna.683308
|View full text |Cite
|
Sign up to set email alerts
|

PNPase is a key player in the regulation of small RNAs that control the expression of outer membrane proteins

Abstract: In this report, we demonstrate that exonucleolytic turnover is much more important in the regulation of sRNA levels than was previously recognized. For the first time, PNPase is introduced as a major regulatory feature controlling the levels of the small noncoding RNAs MicA and RybB, which are required for the accurate expression of outer membrane proteins (OMPs). In the absence of PNPase, the pattern of OMPs is changed. In stationary phase, MicA RNA levels are increased in the PNPase mutant, leading to a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 46 publications
5
76
1
Order By: Relevance
“…hPNPase old-35 is a 3′, 5′ exoribonuclease that catalyzes the phosphorolysis of RNA, generating nucleoside diphosphates as cleavage products (26). We demonstrated previously that hPNPase old-35 could specifically degrade c-myc mRNA, resulting in growth arrest in human melanoma cells (16). Apart from our study, a number of additional potential substrates for hPNPase old-35 have been identified, including small RNA and noncoding RNA.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…hPNPase old-35 is a 3′, 5′ exoribonuclease that catalyzes the phosphorolysis of RNA, generating nucleoside diphosphates as cleavage products (26). We demonstrated previously that hPNPase old-35 could specifically degrade c-myc mRNA, resulting in growth arrest in human melanoma cells (16). Apart from our study, a number of additional potential substrates for hPNPase old-35 have been identified, including small RNA and noncoding RNA.…”
Section: Discussionmentioning
confidence: 55%
“…Analysis of the expression profile of hPNPase old-35 revealed that it is predominantly a type I IFN-inducible gene and might play an essential role in IFN-induced growth arrest in human melanoma cells by executing its exonuclease activity on c-myc mRNA (12)(13)(14)(15). Apart from c-myc mRNA degradation, hPNPase old-35 is also involved in regulating the levels of several small noncoding RNAs (16). Very recently, Wang et al (17) reported that hPNPase old-35 , along with human mitochondrial SUV 3 (suppressor of Var1 3), degrades dsRNA in the 3′-to-5′ direction.…”
mentioning
confidence: 99%
“…36 A major role of PNPase in the turn-over of several small RNAs that control expression of outer membrane proteins was demonstrated in E. coli. 37 In general little is known to date on different levels or activities of RNases or their different organization in protein complexes in different growth phases.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this protection of the 3′ end will not only help stabilize the respective RNA (13), but also suggests a pathway for freshly transcribed sRNAs to actively switch off the effects of other, preexisting sRNAs in a rapid way, simply by competing them out from Hfq and exposing them to accelerated degradation. Indeed, Hfq has been found to protect the primary RNA 3′ end of both mRNAs from oligoadenylation by poly(A) polymerase I (5) and sRNAs from degradation mediated by polynucleotide phosphorylase (29).…”
Section: The Free 3′-terminal Hydroxyl Group Is Crucial For the High-mentioning
confidence: 99%